Curating and Cultural Difference in the Iberian Context. From Difference to Self-Reflexivity (and Back Again?) - Garrido Castellano, Carlos (2018)
This article analyzes how curatorial practices deal with coloniality and, in a broader sense, with the legacies of colonialism and imperialism in our postcolonial present. To do so, it approaches the curatorial landscape of the Iberian territories in a moment of a radical geopolitical transformation, marked by the inclusion of Portugal and Spain in the European Union, the critical responses to the commemoration of their imperial past, and the rethinking of their postcolonial, post-dictatorial identity. Frequently framed from the point of view of exceptionalism, in a separated way, this article argues that Iberian postcoloniality can be better understood when approached from a comparative perspective.